Neighborhood poverty, intergenerational mobility, and early developmental health in a population birth cohort. (March 2022) - Hackman, Daniel A.; Suthar, Himal; Palmer Molina, Abigail; Dawson, William C.; Putnam-Hornstein, Emily
Abstract: Living in a neighborhood with high levels of intergenerational mobility is associated with better childhood cognition and behavior as well as adult health. Nevertheless, it is unclear if such differences originate earlier, and thus if neighborhood intergenerational mobility is associated with health differences at birth. To address this question, we examined whether neighborhood intergenerational mobility, independent of neighborhood poverty, was associated with low birth weight (LBW) in a population-based cohort of singleton children born in California in 2017 ( n  = 426, 873). Although increased neighborhood mobility was associated with a decreased likelihood of LBW, it was no longer associated with LBW (OR = 0.98, CI = 0.96, 1.00) after adjusting for neighborhood poverty. Meanwhile, neighborhood poverty was associated with LBW (OR = 1.04, CI = 1.02, 1.05) after accounting for mobility, with the odds of LBW 9.4% higher among children born where neighborhood poverty was in the 90th percentile compared with children born where neighborhood poverty was in the 10th percentile. Findings indicate that neighborhood poverty, but not intergenerational mobility, is a robust and independent correlate of increased LBW births, and thus early developmental health. These findings also suggest that the role of neighborhood intergenerational mobility in child and adult health outcomes may emerge later in development, independent of LBW, or that the role of neighborhood intergenerational mobility in LBW may be indirectly mediated through exposure to neighborhood poverty. Highlights: It is unknown whether neighborhood intergenerational mobility is associated with low birth weight (LBW). Neighborhood poverty accounted for the association between intergenerational mobility and LBW in a population-based cohort. Odds of LBW were higher for children from high poverty neighborhoods, accounting for intergenerational mobility. Neighborhood poverty is important for early prevention, while neighborhood intergenerational mobility may be important later.